2014
DOI: 10.1073/pnas.1400556111
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis of the ATAD2 bromodomain

Abstract: Due to the emerging importance of the bromodomain binding region in the study of epigenetic effectors and the vast implications for a wide variety of human disease, the bromodomain region of human ATPase family AAA+ (ATPases associated with diverse cellular activities) domain-containing protein 2 (ATAD2) was targeted for chemical synthesis. The ATAD2 bromodomain (130 aa) was divided into five strategic fragments to be assembled using native chemical ligation with a focus on maximal convergency and efficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Discovery of the ATAD2 gene is a new breakthrough in oncology research. The AAA+ ATPase structure domain is a molecular chaperone using ATP activity to participate in the activities of cells, cell cycle control, signal transduction, and gene expression regulation (15). The bromine structure domain and acetylation of the lysine model adjust chromosome remodeling and transcriptional control of the interaction between proteins (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Discovery of the ATAD2 gene is a new breakthrough in oncology research. The AAA+ ATPase structure domain is a molecular chaperone using ATP activity to participate in the activities of cells, cell cycle control, signal transduction, and gene expression regulation (15). The bromine structure domain and acetylation of the lysine model adjust chromosome remodeling and transcriptional control of the interaction between proteins (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we and others have shown that increased ATAD2 may predict survival, and we here confirm that ATAD2 protein assessed by IHC is an independent prognostic marker in endometrioid endometrial cancer patients. Combined with the increased efforts to target bromodomain-containing proteins in cancer [ 15 , 26 ], ATAD2 seems an attractive cancer protein for more detailed studies. It is also interesting that our molecular analyses point to PI3K-pathway and HDAC inhibitors as potential drugs for treatment of patients with high ATAD2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its N-terminal part that interacts with E2F and AR, ATAD2 consists of a bromodomain capable of binding to acetylated histones, and the AAA ATPase domain that possesses ATPase activity and mediates protein multimerization [ 4 , 5 , 13 ]. Both the bromodomain and the AAA ATPase domain could be targeted by small molecule inhibitors, and the recent chemical synthesis of the ATAD2 bromodomain could facilitate further studies of the function of the protein [ 15 ]. Combined with its apparent wide overexpression in cancers, this leaves ATAD2 as a promising target for therapy in several cancers and calls for further investigations of its expression in specific cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…Danishefsky's group then applied this approach to the chemical synthesis of hPTHrP and ATAd2 [80,81]. hPTHrP is a protein widespread in human tissues.…”
Section: Ligation At Leucine Sitementioning
confidence: 99%
“…This 130-mer peptide was assembled from five fragments via one Cys-ligation and three Leu-ligations in a highly convergent manner with only three total RP-HPLC events. The global desulfurization was also achieved under metalfree conditions [81].…”
Section: Ligation At Leucine Sitementioning
confidence: 99%